Development of the system calculation and analytical indicators characterizing the regional passenger transport - E. А. Makarova; S. V. Muktepavel (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The increase of passengers’ traffic volume and maintenance of stable positions on transport market are priority tasks for JSC FPC. Development of marketing shares and new offers for passengers’ service are based on studying regional features of demand and relevant state of transport services for different types of passenger traffics. System of calculating and analytical indicators for regional passenger traffic is presented in this article. It allows specialists in marketing tasks making researches of passenger flows tendencies, determining demand and price factor levels of transport services, obtaining scheme of correspondence dispersion across the region, making comparative analysis of JSC FPC internal passenger traffic in total amount of passenger traffic in the network. In practice this analytical information can be used to rationalize optimal passenger train length, to assess reasonability of putting into operation local trains, to define optimal stops quantity and to calculate necessities in fleet of passenger cars to satisfy demand.